Statistical Modeling and Factors Influencing School Dropout in Indonesia: A Review - Shanty, Meyrna Vidya; Mahadtir, Muhamad; Awaluddin, Awaluddin; Natalia, Derliani; Ramadani, Reski Aulia; Aswi, Aswi (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
The education enrollment rate is crucial for Indonesia to improve its human resources and sustain its economic development. In reality, the dropout student rate is still relatively high. Previous research has highlighted several factors and models related to the dropout student rate in Indonesia. The purpose of the study is to identify the most popular statistical modeling and factors influencing school dropout in Indonesia. We searched in February 2023 using ScienceDirect, ProQuest, and Google Scholar. The search was restricted to refereed journal articles published in English from January 2013 to December 2022. This study underwent four stages: identification, screening, eligibility, and inclusion. The study finds that the most popular statistical modeling is the Logistic Regression Model, and the most significant factor increasing the school dropout rate in Indonesia is family and economic factors. The findings suggest that children who were not attending school came from families with lower levels of education. The well-being of these families was directly linked to their children's educational status. The primary reasons for young students dropping out of elementary and junior schools include an inability to pay school fees and a desire to work on farms to support their parents.